Pressure Relief and Permeability Enhancement Mechanism of Short-Distance Floor Roadway in Deep Coal Roadway Strip - Benqing Yuan; Min Tu; Jianjun Cao; Xiang Cheng (Geofluids)
A pressure relief and permeability enhancement method through short-distance floor roadway was proposed to solve the difficult outburst prevention during the gas extraction at the coal roadway strips in deep outburst coal seams with high ground stress and low gas permeability. On the basis of an equivalent model of the surrounding rock in a deep roadway, the analytical solutions of deep roadway excavation to the stress and deformation of pressure relief at overlying short-distance coal roadway strips were obtained using the unified strength theory and nonassociated flow rules. Next, the criteria for determining the reasonable position of floor roadway were established, and a mechanical model of short-distance floor roadway for the pressure relief and permeability enhancement zone at the overlying coal seam was constructed. Finally, the scope of the zonal disintegration at the coal roadway strips in the elastic and elastic–plastic zones of the surrounding rock in the roadway, as well as the expression of gas permeability change, was given. The engineering trial calculation and practice showed that the stress and strain of the surrounding rock in the roadway were evidently influenced by the intermediate principal stress coefficient. Moreover, the vertical stress and vertical displacement of overlying coal seam were gradually reduced with the increase in the intermediate principal stress coefficient and vertical distance of the floor roadway. The minimum reasonable distance arranged for the 213 floor roadway in Qujiang Coal Mine was 6.21 m, and the effective pressure relief should be conducted within 10.6 m from the coal seam floor. When the pressure relief was located at 9.0 m from the coal seam floor, the investigation results were basically consistent with the theoretical analysis results, exerting obvious pressure relief and permeability enhancement effects on the overlying short-distance coal roadway strips.